Patent Urachus with Bladder Prolapse - Thapa, B; Pun, MS (Journal of Nepal Paediatric Society, 2014)
We report a case of bladder prolapse through a patent urachus in a term male neonate with a large, red, tubular, mucosa lined mass inferior to the umbilical cord. A cystic mass communicating with fetal urinary bladder was detected in an antenatal ultrasound in a 26 years primigravida at 18 and 26 weeks gestation. The cyst disappeared at 35 weeks and a new solid mass was noted at the fetal abdominal wall. After birth a protruded mucosal mass inferior to the umbilical cord was noted. Urethral catherisation confirmed communication with bladder. On the second day of life excision of urachus, repair, reduction of bladder and reconstruction of abdominal wall was performed. The patient voided well and was discharged on ninth day without any complication. DOI: http://dx.doi.org/10.3126/jnps.v34i1.7877 J Nepal Paediatr Soc 2014;34(1):68-70